What next in fundamental physics in space. Issue 1 (24th November 2015) - Battiston, R.
Abstract : Modern fundamental science is unbelievably young. During the last few centuries physics has made gigantic steps, sometimes revolutions, still today we address in a convincing manner only a pitiful 5% of the universe around us. The theoretical framework which let us understand the 5% tells us that there is a 95% of new forms of energy and matter to be discovered and understood. It is likely that in order to find the answer to these fundamental issues we should turn our attention to the same field which has spurred them: the Universe and the flood of radiation which is reaching us from its depths. Abstract : With the discovery of the Higgs boson the SM is complete and we are looking for the remaining 95% of the universe. Astroparticle physics carries promises to deliver some answers to this basic question. In this paper I try to explain why.